AbobotulinumtoxinA in the management of cervical dystonia in the United Kingdom: a budget impact analysis - Abogunrin S; Br; S; Desai K; Dinet J; Gabriel S; Harrower T (Dove Medical Press, 2015)
Seye Abogunrin,1 Sarah Brand,2 Kamal Desai,3 Jerome Dinet,4 Sylvie Gabriel,5 Timothy Harrower61Meta Research, Evidera, London, UK; 2Health Economics, Evidera, Bethesda, MD, USA; 3Health Economics, Evidera, London, UK; 4Health Economics and Outcomes Research (Global), 5Global Market Access and Pricing, Ipsen Pharma, Boulogne-Billancourt, France; 6Royal Devon and Exeter NHS Foundation Trust, Exeter, UKBackground: Cervical dystonia (CD) can be effectively managed by a combination of botulinum neurotoxin A (BoNT-A) and conventional therapy (skeletal muscle relaxants and rehabilitative therapy), but the costs of different interventions in the UK vary.Methods: A budget impact model was developed from the UK payer perspective with a 5-year time horizon to evaluate the effects of changing market shares of abobotulinumtoxinA, nabotulinumtoxinA, and incobotulinumtoxinA, and best supportive care from the UK payer perspective. Epidemiological and resource use data were retrieved from the published literature and clinical expert opinion. Deterministic sensitivity analyses were performed to determine the parameters most influential on the budgetary findings under base case assumptions.Results: Under base case assumptions, an increased uptake of abobotulinumtoxinA showed an accumulated savings of £2,250,992 by year 5. Treatment per patient per year with onabotulinumtoxinA and incobotulinumtoxinA costs more when compared to treatment with abobotulinumtoxinA. One-way sensitivity analyses showed that the prevalence of CD, dose per injection of each of the BoNT-As, and time to reinjection of incobotulinumtoxinA and abobotulinumtoxinA influenced the base case findings most.Conclusion: There is potential for cost savings associated with the greater use of abobotulinumtoxinA rather than other BoNT-A treatments, permitting more patients to benefit more from effective BoNT-A treatment with a fixed budget. Keywords: cervical dystonia, torticollis, botulinum toxin A, budget impact analysis